Modeling the Drivers of Blockchain-Based AI Adoption to Improve Financial Transparency in Health Insurance Organizations - Mohammadi Tong Andri MSc Public Administration, Sepideh; Mohammadi Tang Andri, MSc, Information Technology Management , Sahar (Blockchain in Healthcare Today, 2025)
This research explores the primary organizational and environmental factors that influence the adoption of blockchain-integrated artificial intelligence (AI) systems aimed at enhancing financial transparency within health insurance institutions. Building on established models of technology acceptance and organizational change, a conceptual framework was developed to examine the interaction of technological readiness, management support, regulatory compliance, and workforce capability. Data collected from 272 professionals working in various health insurance entities were analyzed using structural equation modeling (SEM) to assess both direct and indirect pathways. The findings underscore that internal drivers—particularly employee training, executive leadership commitment, and digital infrastructure—are far more significant in shaping adoption outcomes than external forces like regulatory mandates or market competition. Moreover, financial transparency emerges as both a critical outcome and a mediating factor that reinforces trust in technology adoption. This study offers practical insights for policymakers and healthcare administrators aiming to promote ethical, efficient, and transparent digital transformation in the insurance sector.